2001
DOI: 10.1074/jbc.m011331200
|View full text |Cite
|
Sign up to set email alerts
|

FtsY Binds to the Escherichia coli Inner Membrane via Interactions with Phosphatidylethanolamine and Membrane Proteins

Abstract: Targeting of many polytopic proteins to the inner membrane of prokaryotes occurs via an essential signal recognition particle-like pathway. FtsY, the Escherichia coli homolog of the eukaryotic signal recognition particle receptor ␣-subunit, binds to membranes via its amino-terminal AN domain. We demonstrate that FtsY assembles on membranes via interactions with phosphatidylethanolamine and with a trypsin-sensitive component. Both interactions are mediated by the AN domain of FtsY. In the absence of phosphatidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
54
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 41 publications
7
54
1
Order By: Relevance
“…15 and this study), we show that the MTS is highly dynamic in solution. Previous studies showed that FtsY has a preference for anionic phospholipids (9), whereas other studies also suggested a role of zwitterionic lipids (36). The current study clarifies that only the interaction with anionic phospholipids triggers a random-coil helix transition of the MTS.…”
Section: Discussionsupporting
confidence: 61%
“…15 and this study), we show that the MTS is highly dynamic in solution. Previous studies showed that FtsY has a preference for anionic phospholipids (9), whereas other studies also suggested a role of zwitterionic lipids (36). The current study clarifies that only the interaction with anionic phospholipids triggers a random-coil helix transition of the MTS.…”
Section: Discussionsupporting
confidence: 61%
“…20). This proposal has been confirmed several times by demonstrating that FtsY assembles on membranes via interactions with a trypsin-sensitive component (22,37). Finally, the most compelling evidence for FtsYmembrane protein association has recently been offered by studies of the interaction between FtsY and the SecYEG complex in E. coli (11,12).…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, at least one determinant of lipid interaction was identified as the NG domain. In contrast to acidic lipids, other studies proposed that FtsY assembles on membranes via interactions with phosphatidylethanolamine, through the AN domain (37). Regardless of the crucial differences in identifying the specific lipids (see later), the combined studies implied a role for the N-domain in lipid binding.…”
Section: Discussionmentioning
confidence: 94%
“…Strong support for functional interaction of FtsY with lipids, preferentially acidic ones, was obtained by in vitro studies, which demonstrated marked stimulation of the FtsY GTPase activity by lipids (15). On the other hand, it has been shown that a postulated FtsY membrane assembly domain binds to E. coli inner membrane inverted vesicles via an interaction with a trypsin-sensitive component (28) and that FtsY is associated with the translocon (7,8). Based on these and additional data, a model was proposed that FtsY binding to the membrane occurs initially through phospholipid binding, followed by targeting to translocation sites via an interaction with an unknown membrane protein.…”
Section: Discussionmentioning
confidence: 97%